2011
DOI: 10.1016/j.jhep.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The heart in liver transplantation

Abstract: The heart and liver are organs that are closely related in both health and disease. Patients who undergo liver transplantation may suffer from heart disease that is: (a) related to the original cause of the liver disease such as hemochromatosis, (b) related to the liver disease itself, or (c) related to other associated conditions. Furthermore, liver transplantation is one of the most cardiovascular stressful events that a patient with cirrhosis may undergo. After liver transplantation, the progression of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 166 publications
1
57
0
Order By: Relevance
“…Evidence suggests that the activity of the guanylate cyclase system is increased with worsening severity of liver failure [13]. This may explain the increased prevalence of adverse intraoperative cardiovascular events in patients who have a greater severity of illness due to liver disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the activity of the guanylate cyclase system is increased with worsening severity of liver failure [13]. This may explain the increased prevalence of adverse intraoperative cardiovascular events in patients who have a greater severity of illness due to liver disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decompensated cirrhotics with a high degree of portal hypertension have a prolonged QT interval, due to electrolyte disturbances or the use of QT interval-prolonging drugs, that need correction [34]. Although, in normal hemodynamic conditions, echocardiography is an excellent tool to assess the presence of systolic or diastolic dysfunction, generally cirrhotics are affected by a hyperdynamic syndrome; this hemodynamic disturbance influences the cardiac load and makes an accurate evaluation of cardiac function through conventional echocardiography more difficult [34].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…Although, in normal hemodynamic conditions, echocardiography is an excellent tool to assess the presence of systolic or diastolic dysfunction, generally cirrhotics are affected by a hyperdynamic syndrome; this hemodynamic disturbance influences the cardiac load and makes an accurate evaluation of cardiac function through conventional echocardiography more difficult [34].…”
Section: Pre-transplant Investigative Methodsmentioning
confidence: 99%
“…[3][4][5][6][7] Cirrhotic cardiomyopathy becomes clinically apparent mostly after exposition to physical stress 4 and increases risk for fatal complications after liver transplantation or after implantation of a transjugular intrahepatic portosystemic shunt. 3,4,8,9 Recent studies provide evidence that hypertrophy of the left ventricle, left-atrial dilatation, and increased enddiastolic and end-systolic left-ventricular volume may be more frequent in patients with liver cirrhosis. 4,8,10 Most recently, a high prevalence of cardiac arrhythmia, for example, atrial fibrillation has been demonstrated.…”
mentioning
confidence: 99%